1992
DOI: 10.1002/mc.2940050406
|View full text |Cite
|
Sign up to set email alerts
|

Efficient protection against oxidative DNA damage in chromatin

Abstract: The role of histones and higher order chromatin structures in protecting against oxidative DNA damage was investigated using an in vitro system consisting of nuclear and nucleoid monolayers as model chromatin substrates. These substrates, derived from human skin fibroblasts, were challenged with hydroxyl radicals produced via a Fenton reaction involving Fe(II)-ethylenediaminetetraacetic acid and ascorbic acid. The resulting DNA strand breaks were measured using the alkaline unwinding technique. The sequential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
2
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(79 citation statements)
references
References 35 publications
4
70
2
3
Order By: Relevance
“…Instead, groups have been using ␥-rays (47) and x-rays (24,48) to generate hydroxyl radicals in vivo. The group utilizing x-rays noted that a 10-fold higher dose was required to obtain the same level of strand cleavage as obtained in vitro, in support of previous studies showing that chromatin greatly protects DNA from hydroxyl radical damage (49,50). We found that the Fe-EDTA system gave the same cleavage pattern for the FOS promoter nucleosome in HeLa cells as produced by x-rays in TIG-3 cells (24).…”
Section: Discussionsupporting
confidence: 85%
“…Instead, groups have been using ␥-rays (47) and x-rays (24,48) to generate hydroxyl radicals in vivo. The group utilizing x-rays noted that a 10-fold higher dose was required to obtain the same level of strand cleavage as obtained in vitro, in support of previous studies showing that chromatin greatly protects DNA from hydroxyl radical damage (49,50). We found that the Fe-EDTA system gave the same cleavage pattern for the FOS promoter nucleosome in HeLa cells as produced by x-rays in TIG-3 cells (24).…”
Section: Discussionsupporting
confidence: 85%
“…The experiment with the DNA-PLT films sheds some light on the possible involvement of mechanism (2). Thermodynamically tyrosine will compete with guanine as a hole trap.…”
Section: Holes Formed On the Dna Sugar-phosphate Backbone Transfer Tomentioning
confidence: 95%
“…This DNA-protein complex has long been known to confer protection of DNA against radiation damage (1). Radiosensitivity of DNA, quantified as the yield of double-strand breaks (DSBs), was demonstrated to increase on going from intact cells to naked DNA, with the partially stripped chromatin being intermediate in this order (2,3). Stepwise removal of DNAbound proteins from the chromatin increases the amount of radiation-induced DSBs (4,5), with removal of core histones having the largest impact on the radiosensitivity of DNA (5).…”
Section: Introductionmentioning
confidence: 99%
“…Пе-рестройки хроматина, сборка и разборка нуклеосом сопровождают все процессы, происходящие с учас-тием генетического материала в клетке. Нарушения процессов ДНК-гистоновых и гистон-гистоновых взаимодействий и необратимая потеря нуклеосом в результате действия различных факторов способ-ны запускать патологические процессы и снижать жизнеспособность клеток, приводя, в частности, к блокировке процессов транскрипции [7][8][9].…”
unclassified
“…№ 1. C. [3][4][5][6][7][8] нена в связи с большими размерами и структурной лабильностью. Поэтому основным методом полу-чения структурной информации в данном случае служит просвечивающая электронная микроскопия (ПЭМ) макромолекул [10].…”
unclassified